Impact of HMG‐CoA reductase inhibitors on the incidence of polyomavirus‐associated nephropathy in renal transplant recipients with human BK polyomavirus viremia. Issue 4 (26th June 2015) - Gabardi, S.; Ramasamy, S.; Kim, M.; Klasek, R.; Carter, D.; Mackenzie, M.R.; Chandraker, A.; Tan, C.S.
Abstract Background Up to 20% of renal transplant recipients (RTR) will develop human BK polyomavirus (BKPyV) viremia. BKPyV viremia is a pre‐requisite of polyomavirus‐associated nephropathy (PyVAN). Risk of BKPyV infections increases with immunosuppression. Currently, the only effective therapy against PyVAN is reductions in immunosuppression, but this may increase the risk of rejection. In vitro data have shown that pravastatin dramatically decreased caveolin‐1 expression in human renal proximal tubular epithelial cells (HRPTEC) and suppressed BKPyV infection in these cells. Based on these data, we postulated that statin therapy may prevent the progression of BKPyV viremia to PyVAN. Patients and methods A multicenter, retrospective study was conducted in adult RTR transplanted between July 2005 and March 2012. All patients with documented BKPyV viremia (viral load >500 copies/mL on 2 consecutive tests) were included. Group I consisted of patients taking a statin before the BKPyV viremia diagnosis (n = 32), and Group II had no statin exposure before or after the BKPyV viremia diagnosis (n = 36). The primary endpoint was the incidence of PyVAN. Results Demographic data, transplant characteristics, and the degree of immunosuppression (i.e., induction/maintenance therapies, rejection treatment) were similar between the groups, with the exception of more diabetics in Group I. The incidence of PyVAN was comparable between the 2 groups (Group I = 28.1% vs. Group II = 41.7%; P = 0.312). Conclusions Despite the proven in vitro effectiveness of pravastatin preventing BKPyV infection in HRPTEC, statins at doses maximized for cholesterol lowering, in RTR with BKPyV viremia, did not prevent progression to PyVAN.